(untitled) (Konferensiyalar | Conferences, 2024)
Recent research has predominantly examined various linguistic concepts in different languages, but there has been limited exploration into how the concept of "Labor" is articulated when comparing English to Uzbek. This study aims to delve into the representation of the concept of "Labor" in Uzbek and English languages, specifically through proverbs. It compares how these expressions reflect the importance of hard work, determination, and the belief that effort leads to success. By studying these common expressions in the two languages, the article highlights the shared value placed on working hard and persisting to achieve goals in different cultural settings.